Age‐dependent decline in fin regenerative capacity in the short‐lived fish Nothobranchius furzeri. Issue 5 (29th June 2015) - Wendler, Sebastian; Hartmann, Nils; Hoppe, Beate; Englert, Christoph
Summary The potential to regenerate declines with age in a wide range of organisms. A popular model system to study the mechanisms of regeneration is the fin of teleost fish, which has the ability to fully regrow upon amputation. Here, we used the short‐lived killifish Nothobranchius furzeri to analyse the impact of aging on fin regeneration in more detail. We observed that young fish were able to nearly completely (98%) regenerate their amputated caudal fins within 4 weeks, whereas middle‐aged fish reached 78%, old fish 57% and very old fish 46% of their original fin size. The difference in growth rate between young and old fish was already significant at 3 days post amputation (dpa) and increased with time. We therefore hypothesized that early events are crucial for the age‐related differences in regenerative capacity. Indeed, we could observe a higher percentage of proliferating cells in early regenerating fin tissue of young fish compared with aged fish and larger fractions of apoptotic cells in aged fish. Furthermore, young fish showed peak upregulation of several genes involved in fgf and wnt/β‐catenin signalling at an earlier time point than old fish. Our findings suggest that regenerative processes are initiated earlier and that regeneration overall is more efficient in younger fish.